2022
DOI: 10.3390/w14132041
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Evaluation of Canopy Resistance Models for Estimating Evapotranspiration over a Drip-Irrigated Potato Crop in Southern Chile under Water-Limited Conditions

Abstract: The evapotranspiration () process is an essential component in many agricultural water management systems, and its estimation is even more determinant when crops are grown under water-limited environments. The traditional canopy resistance () approaches were evaluated to simulate potato evapotranspiration () using the original Penman–Monteith equation under different irrigation levels. A field study was carried out on a drip-irrigated potato crop (var. Puyehue INIA) located in the Research Center Carillanca (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
3
1
0
Order By: Relevance
“…Regarding diurnal patterns, the tendency of the estimated half-hourly Rc had a similar magnitude, along the growth stages. Averaged midday Rc values around 15 s m −1 were similar to those reported for potato by Amer & Hatfield (2004) and López-Olivari et al (2022) and lower than values reported by Kjelgaard & Stockle (2001) (midday Rc values close equal to 40 s m −1 ). As seen for daily data, diurnal aerodynamic resistance generally was higher than canopy resistance.…”
Section: Crop Development Surface Resistance and Carbon -Water Fluxessupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding diurnal patterns, the tendency of the estimated half-hourly Rc had a similar magnitude, along the growth stages. Averaged midday Rc values around 15 s m −1 were similar to those reported for potato by Amer & Hatfield (2004) and López-Olivari et al (2022) and lower than values reported by Kjelgaard & Stockle (2001) (midday Rc values close equal to 40 s m −1 ). As seen for daily data, diurnal aerodynamic resistance generally was higher than canopy resistance.…”
Section: Crop Development Surface Resistance and Carbon -Water Fluxessupporting
confidence: 78%
“…This expected low canopy resistance under wellwatered conditions has been reported by other researchers (Aires et al, 2008;Kumagai et al, 2008;Paulino Junior and Silva von Randow, 2017;Souza et al, 2012). Unlike with López-Olivari et al (2022), we observed a larger aerodynamic resistance (generally higher than Rc) indicating more importance of Ra in total resistance to water vapor transport. Regarding diurnal patterns, the tendency of the estimated half-hourly Rc had a similar magnitude, along the growth stages.…”
Section: Crop Development Surface Resistance and Carbon -Water Fluxessupporting
confidence: 73%
“…At the diurnal half-hourly scale in the well-watered conditions FI site, we observed higher ET, GPP, and sink activity (more negative NEE) during the lowest Rc, which evidence an intense carbon-water exchange under a low bulk resistance to mass transfer (Amer and Hatfield 2004;Aires et al 2008;Kumagai et al 2008;Souza et al 2012; Paulino Junior and Silva von Randow 2017; Wehr and Saleska 2021) that supports a higher CO2 sequestration activity. Our midday Rc values around 15 s m −1 were like those reported for potato by Amer and Hatfield (2004) and López-Olivari et al (2022) and lower than values reported by Kjelgaard and Stockle (2001) (40 s m−1). In the DI site, ET continues at a high rate while there is a high restriction in the GPP and NEE fluxes.…”
Section: Crop Development Surface Resistance and Carbon -Water Fluxessupporting
confidence: 56%
“…The second approach, known as the micrometeorological method, uses a scientific understanding of the physics of evapotranspiration. Mathematical relationships have been developed to describe these processes through two fundamental climatological components: energy balance and mass transport [10,[17][18][19]. The third method centers on developing empirical relationships that are often site-specific and based on regional climatological conditions and often used in regression analysis.…”
Section: Introductionmentioning
confidence: 99%